Assessment of college students awareness about tuberculosis in Moradabad - A, Khan N; M, Abid; K, Singh V; V, Vaishali; P, Chattopadhyay; K, Ghosh A; K, Kamal (Indian Journal of Pharmacy Practice)
Lack of knowledge and awareness about Tuberculosis (TB) as well as Direct observed therapy short course (DOTS) are a persistent and major community problem due to which suffering and mortality rate increases tremendously. So it is responsibility of pharmacists to develop a common awareness for prevention, care and treatment of TB in the community. This survey is strictly based on assessing the awareness about TB among undergraduate (UG) and postgraduate (PG) students of nonmedical stream in Institute of Foreign Trade & Management, Moradabad (U.P.) India. In the present study, 59.41% were male and 52.78% were female. 60.81% P.G. students and 54.31 % UG students were answered among them. It represents that male student's awareness were higher than the female students. The survey results also revealed that both UG& PG students of I.F.T.M. possessed very poor knowledge about type of TB, multi drug resistance (MDR) & Mantaux test, and the knowledge of UG students was very poor as compared to PG students. Pharmacists should realise their role in health education programs in the community to improve the public awareness about health burden diseases like tuberculosis.
Keywords: Directly observed therapy short course; multi drug resistance; mass miniature radiography; National Tuberculosis Control Programme